What's wrong with work? / Lynne Pettinger. - Pettinger, Lynne (21st century standpoints., 2023)
What's wrong with work shows that how workers are treated has wide implications beyond the lives of workers themselves. Recognising gender, race, class and global differences, the book considers the ways formal work is often dependent on informal work and concludes by considering what might make work better.